Animal dung from arid environments and archaeobotanical methodologies for its analysis: An example from animal burials of the Predynastic elite cemetery HK6 at Hierakonpolis, Egypt. (1st February 2013) - Marinova, Elena; Ryan, Philippa; Van Neer, Wim; Friedman, Renée
<x xml:space="preserve">Abstract</x> Bioarchaeological studies of animal dung from arid environments provide valuable information on various aspects of life in ancient societies relating to land use and environmental change, and from the Neolithic onwards to the animal husbandry and the use of animals as markers of status and wealth. In this study we present the archaeobotanical analysis of animal gut contents from burials in the elite Predynastic cemetery HK6 at Hierakonpolis, Upper Egypt. The study involved analysis of plant macrofossils, phytoliths and pollen applied on samples from two elephants, a hartebeest, an aurochs and five domestic cattle. The study showed that most probably the elephants were given fodder containing emmer spikelets (dehusking by-products) before the animals death. Most of the other animals were also foddered with cereal chaff, but were mainly allowed to browse and graze in the settlement area and near the Nile. The diet of some contained only wild growing plants. The variety of plant remains identified in the stomach contents indicates that the food plants for the animals were obtained from three possible habitats near the site: the river banks, the low desert and the cultivated/anthropogenically modified areas.